Challenges and incentives for sustainable manure management in Russia - Lindgren, Johanna (SLU/Dept. of Soil and Environment, 2013)
The Baltic Sea is threatened by eutrophication that largely is due to nutrient leaching from farmland within the catchment area. To solve this problem the surrounding countries cooperate within various configurations such as HELCOM and the EU-financed project Baltic Compass. Poor manure management in Russia has been discussed frequently the last couple of years. A literature review of different types of reports and legal acts is the core of this degree project which has been performed in connection to two ongoing research projects financed by EU (Baltic Compass) and SIDA. It is supplemented with interviews with Swedish agricultural consultants and travel reports from two occasions when I had the opportunity to discuss with Russians active within the agricultural sector. Different hypotheses were investigated and discussed. The environmental debate in Russia is quiet and there is a widespread approach that economic profit always trumps environmental concern – a Soviet heritage that influence the Russian agriculture considerably. The Russian legal acts on stable manure management focus mainly on sanitary questions and only secondary on nutrient leaching. If the legislation was fully implemented, the nutrient leaching would decrease significantly. The incentives for obeying the law are low due to corruption and the fact that it is cheaper and easier to pay the fees than fixing the primary cause. Farmers can receive financial support for increased production, but there are no economic instruments to encourage environmental measures. The economic situation on the farms is usually poor and the possibilities to make large investments low, partly due to the difficulties to receive credits on beneficial terms. The common attitude to manure is that is not a resource, but rather a problem to get rid off. In order to improve the situation it is important to increase the knowledge on manure nutrient value and the soil conditioning organic matter. The subsidy on mineral fertilizers is though an important contributing factor to bad manure usage. The development of biogas production in Russia may seem tempting, looking at the amounts of produced manure. But in reality, this is a too big investment for most farmers and the production surplus of gas or electricity cannot be connected to the existing grid. Separation of manure would on the other hand enable longer transports of the P-rich solid fraction, which would improve the nutrient balance on a farm level. Composting of manure is the most common way to treat manure today. If this is done as to minimize nutrient leaching, it could be a good alternative if combined with mineral fertilizers. The manure is used as fertilizers to some extent, but it commonly ends up as a waste in the forests where the risk of nutrient leaching is huge. The concentration of animals in large livestock units is a problem as the spreading area is either too small or too remote from the farm centre.The spreading is further complicated by insufficient drainage systems. I found that the farmers’ incentive for improved manure management and utilization is better economy through increased production rather than environmental issues. In order to enable this, a shift in state priorities is needed as is the development of extention services for increased awareness and knowledge level among farmers.